2023
DOI: 10.1177/15910199231154331
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy alone versus with thrombolysis for ischemic stroke: A meta-analysis of randomized trials

Abstract: Introduction Mechanical thrombectomy (MT) is the standard of care in eligible patients presenting with acute ischemic stroke (AIS). The question of whether intravenous thrombolysis (IVT) improves outcomes in conjunction with MT remains unanswered. We performed a systematic review and meta-analysis of published randomized controlled trials (RCT) to explore outcomes of MT with and without IVT. Methods Following the PRISMA guidelines, a systematic literature review of the English language literature was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…This finding is in agreement with the previously published meta-analyses showing the overall positive effect of bridging-IVT on successful recanalization rates. 2,4 By contrast, in the 2–4 h OTD patients, IVT was not associated with higher rates of target recanalization and was associated with higher rates of HT and poor outcomes. We further demonstrated that the beneficial effect of thrombolysis is higher among patients with OTD below 90 min, and lowest among patients with OTD above 180 min.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This finding is in agreement with the previously published meta-analyses showing the overall positive effect of bridging-IVT on successful recanalization rates. 2,4 By contrast, in the 2–4 h OTD patients, IVT was not associated with higher rates of target recanalization and was associated with higher rates of HT and poor outcomes. We further demonstrated that the beneficial effect of thrombolysis is higher among patients with OTD below 90 min, and lowest among patients with OTD above 180 min.…”
Section: Discussionmentioning
confidence: 88%
“…1 The role of intravenous thrombolysis (IVT) as a bridging treatment prior to EVT is still debatable. Although current guidelines advocate for IVT treatment in all eligible LVO cases, 1 studies examining bridging treatment, including six randomized control trials and several meta-analyses, [2][3][4] have demonstrated inconclusive results. Finding subpopulations that may benefit or conversely be harmed by the IVT + EVT approach may allow better patient selection that could potentially lead to improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis of all 4 large core trials demonstrated that while symptomatic ICH was greater with EVT, clinical/outcome benefit persisted. 2…”
Section: Ischemic Strokementioning
confidence: 99%
“…Thrombectomy trials for large ischemic cores including an extended time window have shown promise. 1–3 The debate on hemodynamic management after endovascular therapy (EVT) for acute ischemic stroke persists, increasingly suggesting that generalized blood pressure (BP) reduction may be harmful. Further investigations explore a potential role for precision medicine.…”
mentioning
confidence: 99%
“…Over the last decade, studies have showcased a clear benefit of endovascular thrombectomy (EVT) over medical therapy (MEDT) alone in managing acute ischemic stroke (AIS) due to large vessel occlusion (LVO) (1). Therefore, current guidelines advocate for EVT in individuals presenting with Alberta Stroke Program Early CT Score (ASPECTS) ≥6 (range: 0-10, inverse relation with the infarction size) (2,3).…”
Section: Introductionmentioning
confidence: 99%